Heuristic methods for the leather nesting problem in the automotive industry - Pinto, Telmo (2016)
In this paper, we address a real leather nesting problem (LNP) with holes and quality zones that arises in the automotive industry. We describe two approaches for the solution of the LNP. The first approach consists in a constructive heuristic, while the second relies on local search methods. The constructive heuristic is based on a simulation of the positioning of a piece so as to evaluate its fitness within the hide and within the current layout. The later approach suggested in this paper is based in a local search method whose neighbourhood structure operates on cutting patterns. In order to improve this procedure, we also describe an improvement of our constructive heuristic to apply it at each iteration of the local search procedure. The proposed methods were implemented and tested on real instances of the automotive industry. The obtained results for both heuristics illustrate the adequacy and the potential of the proposed approaches.